Social and Psychophysiological Consequences of the COVID-19 Pandemic: An Extensive Literature Review - Clemente-Suárez, Vicente Javier; Dalamitros, Athanasios A.; Beltran-Velasco, Ana Isabel; Mielgo-Ayuso, Juan; Tornero-Aguilera, Jose Francisco (Frontiers in Psychology, 2020)
The Coronavirus Disease 2019 (COVID-19) pandemic, now a global health crisis, has surprised health authorities around the world. Recent studies suggest that the measures taken to curb the spread of the COVID-19 outbreak have generated issues throughout the population. Thus, it is necessary to establish and identify the possible risk factors related to the psychosocial and psychophysiological strain during the COVID-19 outbreak. The present extensive literature review assesses the social, psychological, and physiological consequences of COVID-19, reviewing the impact of quarantine measures, isolation, vast human loss, social and financial consequences in the family’s economies, and its impact on the psychological health of the population. We also discussed the effect of psychophysiological factors, considering the impact of physical inactivity and modifications in nutritional habits, at psychological and physiological levels. The present review includes an actualized to date bibliography, articles for which were methodologically analyzed to verify they met the standards of quality and scientific accuracy. Authors understand the pandemic as a multifactorial event for which only a profound and extensive analysis would lead to better compression and efficient intervention in the near future.